Intensive comparative study using X-Ray diffraction for investigating microstructural parameters and crystal defects of the novel nanostructural ZnGa2S4 thin films - Akl, Alaa Ahmed; El Radaf, I.M.; Hassanien, Ahmed Saeed (Superlattices and microstructures, 2020)
This paper is devoted to synthesizing good quality polycrystalline ZnGa2S4 thin films of different thicknesses using inexpensive pyrolysis technology for the first time. Then study the crystal structure, crystal defects and the microstructural properties of these films. The novel ternary ZnGa2S4 thin films are investigated by X-ray diffraction, which exhibited that films have polycrystalline tetragonal nature and their space group is I42‾m(121). The compositional elements of films have been investigated using energy-dispersive X-ray spectroscopy and the result is all synthesized films have good stoichiometry. Field-emission-scanning-electron microscope, FE-SEM is used to study the surface morphology of films. An intensive comparative study has been carried out for studying microstructural parameters and crystal imperfections. The corrected integral breadth, β(rad) of observed diffraction lines have been determined by several distribution functions. Major diffraction lines showed that the integral breadth values decrease gradually as thickness increased, while they increase as increasing the diffraction angle of films. Scherrer and Williamson-Hall equations, both the uniform deformation and uniform stress deformation models and the size-strain plot method have been utilized in this study. The results showed that all films have nanosized dimensions and the crystallite size increases with increasing the thickness. The internal stresses, residual microstrian, and lattice microstain are decreasing as the thickness increased. Along with, the crystal lattice distortion, dislocation density and the number of crystallites are also decreasing. Consequently, increasing the thickness of film samples improves their crystallization and reducing their crystalline defects, too. [Display omitted] •Novel ternary ZnGa2S4 thin-film samples of different thicknesses have been synthesized.•Several distribution functions were applied to estimate the sample broadening.•A comparative intensive study using X-ray diffractograms was achieved.•Microstructural properties and crystal defects of these samples were estimated and discussed.•Increasing thickness led to improve film crystallinity and reduces crystal defects.